Strict conformational demands of RNA cleavage in bulge-loops created by peptidyl-oligonucleotide conjugates. Issue 19 (3rd October 2020) - Staroseletz, Yaroslav; Amirloo, Bahareh; Williams, Aled; Lomzov, Alexander; Burusco, Kepa K; Clarke, David J; Brown, Tom; Zenkova, Marina A; Bichenkova, Elena V
Abstract: Potent knockdown of pathogenic RNA in vivo is an urgent health need unmet by both small-molecule and biologic drugs. 'Smart' supramolecular assembly of catalysts offers precise recognition and potent destruction of targeted RNA, hitherto not found in nature. Peptidyl-oligonucleotide ribonucleases are here chemically engineered to create and attack bulge-loop regions upon hybridization to target RNA. Catalytic peptide was incorporated either via a centrally modified nucleotide (Type 1) or through an abasic sugar residue (Type 2) within the RNA-recognition motif to reveal striking differences in biological performance and strict structural demands of ribonuclease activity. None of the Type 1 conjugates were catalytically active, whereas all Type 2 conjugates cleaved RNA target in a sequence-specific manner, with up to 90% cleavage from 5-nt bulge-loops (BC5-α and BC5L-β anomers) through multiple cuts, including in folds nearby. Molecular dynamics simulations provided structural explanation of accessibility of the RNA cleavage sites to the peptide with adoption of an 'in-line' attack conformation for catalysis. Hybridization assays and enzymatic probing with RNases illuminated how RNA binding specificity and dissociation after cleavage can be balanced to permit turnover of the catalytic reaction. This is an essential requirement for inactivation of multiple copies of disease-associated RNA and therapeutic efficacy.